ANALISIS NOVEL “PUDARNYA PESONA CLEOPATRA” DAN IMPLIKASINYA TERHADAP KESIAPAN MENIKAH - Zahra, Sabina Kaila; Lestari, Melina; Azizah, Rona; Sabila, Najwaa; Maharani, Annisa; Ashadi, Aurellia Nafish (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This study analyzes the novel